Accurate measurements of the bond dissociation energies of 14N2, 14N15N and 15N2 - Liya Lu; Pan Jiang; Hong Gao (Fundamental Research)
Accurate determinations of bond dissociation energies (BDEs) and the corresponding enthalpies of formation derived from them are of fundamental importance, while on the other hand also very challenging in chemistry. In this study, we demonstrate a direct experimental scheme for measuring the BDEs of 14N2, 14N15N and 15N2 to an accuracy of a few wavenumbers. The high-resolution quantum-state-selected velocity-mapped ion images for several rotational levels with accurately known spectroscopic term energies slightly above the dissociation limit N(2D5/2, 3/2) + N(2D5/2, 3/2) were obtained for each of the dinitrogen isotopologue molecules. A linear fit between squares of the radii of the quantum-state-selected images and the spectroscopic term energies gives out an accurate measurement of the threshold D0 for dissociating into the channel N(2D5/2, 3/2) + N(2D5/2, 3/2). The BDEs of 4N2, 14N15N and 15N2 into the lowest channel N(4S) + N(4S) are independently determined to be 78,688 ± 3, 78,705 ± 4 and 78,728 ± 4 cm−1, respectively. These independently determined BDEs are found to give a consistent value of De after considering the zero-point energies for each of the isotopologues, implying the reliability of the present measurement. Comparisons with several previous measurements and theoretical calculations are discussed. The experimental scheme demonstrated in this study should be generally applicable for precisely determining the BDEs of many other diatomic molecules.